AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN SUNGKAI (Peronema canescens Jack) DALAM FORMULASI SIRUP TERHADAP KADAR C-REAKTIF PROTEIN PADA TIKUS PUTIH JANTAN (Rattus norvegicus) YANG DIINDUKSI KARAGENAN - Aztur, Fiorenza Tabina; Simamora, Sarmalina; Nurzana, Nyimas Intan Kemuning; Supriyanti, Yosi (Poltekkes Kemenkes Bengkulu, 2023)
Information that has gone viral in the community is that there is an Indonesian plant that is used as a Covid-19 drug, namely sungkai leaves (Peronema Canescens Jack). This leaf is not well known by some Indonesian people, but its ancestors are often used as herbal therapy. Now Sungkai leaves are very popular. Even though scientific information about the effects of Sungkai leaves has not been found much. The mechanism of action in treating infections due to the corona virus is not yet known, but it is suspected that it can reduce the inflammatory effect. This study aims to examine the anti-inflammatory effect of extracts in Sungkai leaf (Peronema canescens) syrup formulations with different concentrations to obtain the right syrup formula if it does have anti-inflammatory potential. Potential as an anti-inflammatory was measured by its ability to reduce C-Reactive Protein (CRP) levels in the blood serum of male white rats after being induced by intraplantar carrageenan 1% on the right leg. This study used an experimental method with 18 male white rats and was divided into 5 groups, namely group 1 as normal control (only given 1% Na.CMC), group 2 as positive control I (given diclofenac Na), group 3 as positive comparator II (given dexamethasone), group 4 as the treatment group at dose I (given sungkai leaf extract at a dose of 400 mg/200 g BW every day), group 5 as the treatment group at dose II (given sungkai leaf extract at a dose of 600 mg/200 g BW every day). The results of measuring CRP levels in all groups of experimental animals qualitatively using the slide test method showed negative results (no increase in CRP levels).